Health Seeking Behavior for Musculoskeletal Pain of People in Chiang Yun District, Mahasarakham Province. - Ketkowit, Kingkaew; janposri, Witat; Chokkanapitak, jaruwan; Deesri, Pornwipa; Thavondunstid, Prasert (Srinagarind Medical Journal, 2013)
Background : Background : Musculoskeleta pain is a major problem in health. To know the villagers’ seeking behavior will help understand the thinking system, beliefs, and the patterns of treatment of people and will be beneficial in developing the health system. Objective : This research was aimed too study health seeking behavior for musculoskeletal pain of villager laborers and seniors Method : a cross-sectional descriptive study and collecting qualitative data Setting : Chiang Yun District, Mahasarakham Province. Results : It was found that most people used 2 stages in seeking health care for musculoskeletal pain, both mild and severe pain, but the proportion of health seeking in the second stage of severe pain was higher than mild pain. About 65.9% (95% CI : 60.0-71.9) of severe pain used the second stage while the mild pain used only 56.8% (95% CI : 50.9-61.9). The three patterns of treatment often used in mild pain were the following ; a) from massage to self – medication to folk healer, c) from folk healer to self-medication. For severe pain, the three patterns often used were the following ; a) from massage to self-medication, b)from community hospital to private clinic, c) from self-medication to community hospital. Keyword : health seeking behavior, musculoskeletal pain